2005
DOI: 10.1074/jbc.m500331200
|View full text |Cite
|
Sign up to set email alerts
|

JNK1 and JNK2 Oppositely Regulate p53 in Signaling Linked to Apoptosis Triggered by an Altered Fibronectin Matrix

Abstract: The extracellular matrix regulates many cellular processes, including survival, and alterations in the matrix or in matrix survival signals can trigger apoptosis. Previously, we showed that an altered fibronectin matrix triggers apoptosis in primary cells via a novel pathway regulated by transcriptionally mediated decreases in p53 and c-Myc levels. Here we report that this apoptotic mechanism is propagated by decreased phosphorylation of focal adhesion kinase (FAK), which is linked to increased phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 25 publications
(40 reference statements)
1
51
0
Order By: Relevance
“…At the same time, antagonistic functions of JNK1 and JNK2 in regulating of c-Jun have been demonstrated (Sabapathy et al, 2004). It has also been reported that JNK1 and JNK2 oppositely regulate p53 (Fogarty et al, 2003;Tafolla et al, 2005): downregulation of JNK2 by antisense oligonucleotides suppressed p53 levels in primary human fibroblasts, while knockdown of JNK1 resulted in increased levels of p53. Of note, JNK1 and JNK2 can inhibit phosphorylation of each other, apparently by competing for the same upstream kinases (Liu et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At the same time, antagonistic functions of JNK1 and JNK2 in regulating of c-Jun have been demonstrated (Sabapathy et al, 2004). It has also been reported that JNK1 and JNK2 oppositely regulate p53 (Fogarty et al, 2003;Tafolla et al, 2005): downregulation of JNK2 by antisense oligonucleotides suppressed p53 levels in primary human fibroblasts, while knockdown of JNK1 resulted in increased levels of p53. Of note, JNK1 and JNK2 can inhibit phosphorylation of each other, apparently by competing for the same upstream kinases (Liu et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, JNK participates in p53 phosphorylation resulting in p53 accumulation and activation as a transcriptional regulator (Milne et al, 1995;Hu et al, 1997;Fuchs et al, 1998b;Buschmann et al, 2001). The opposite effects of JNK pathway on p53 could be associated with differential function of JNK genes/splice variants (Fogarty et al, 2003;Tafolla et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(23) JNK1 and JNK2 are expressed ubiquitously, whereas JNK3 is expressed restrictively in brain, heart, and testis. (24) The JNK signaling pathway has been implicated in multiple cellular events, such as proliferation, differentiation, survival, and response to extracellular stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that blocking antibodies against the a4 integrin subunit induced apoptosis-like cell rounding in human fibroblasts, similar to that induced by anoikis in response to an altered FN matrix fragment. 2 Integrins mediate those responses by binding ECM ligands and activating signaling cascades that promote these actions. The a4 integrin subunit can bind to at least three interaction sites on FN.…”
mentioning
confidence: 99%